2014
DOI: 10.1007/s10973-014-3841-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chlorogenic acid on the phase transition in phospholipid and phospholipid/cholesterol membranes

Abstract: Chlorogenic acid (CGA) is present in many plants, especially in green coffee, dry plums, and bilberries. It is an important bioactive polyphenol. Studies showed that CGA has an antioxidative, bacteriostatic, anticancer, antiviral, and anti-inflammatory activity. Despite great interest in this compound, its interaction with the lipid model membrane has not yet been investigated. To better understand the relationship between the biological activity of CGA and its interaction with biological membranes, the thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
3
5
0
Order By: Relevance
“…It was shown that the phytoconstituents were positioned within the lipid bilayer, exhibiting high hydrogen binding between the polar site of the lipid bilayer and the hydroxyl groups of 5-caffeoylquinic acid. Pruchnik et al [65] also confirmed the interaction between chlorogenic acid and biological membranes, as verified in this work. The referenced authors evaluated the chlorogenic acid permeation mechanism by differential scanning calorimetry and fluorescence spectroscopy, showing the interaction between chlorogenic acid and the polar site of the biological membrane.…”
Section: In Silico Investigation Based On Molecular Dockingsupporting
confidence: 86%
“…It was shown that the phytoconstituents were positioned within the lipid bilayer, exhibiting high hydrogen binding between the polar site of the lipid bilayer and the hydroxyl groups of 5-caffeoylquinic acid. Pruchnik et al [65] also confirmed the interaction between chlorogenic acid and biological membranes, as verified in this work. The referenced authors evaluated the chlorogenic acid permeation mechanism by differential scanning calorimetry and fluorescence spectroscopy, showing the interaction between chlorogenic acid and the polar site of the biological membrane.…”
Section: In Silico Investigation Based On Molecular Dockingsupporting
confidence: 86%
“…Similarly small changes in thermotropic parameters were observed for the other extracts investigated by us [38][39][40][41][42][43][44].…”
Section: Attenuated Total Reflectance Fourier Transform Infrared Specsupporting
confidence: 68%
“…Therefore, alteration of lipid bilayer properties may result not only in antioxidant action of flavonoids but also in affecting the activity of integral proteins and hence influence transport and other membrane-related processes [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. The ability of polyphenols to penetrate into lipid bilayers is undoubtedly crucial to the protection against oxidation [42].…”
Section: Introductionmentioning
confidence: 99%
“…The study was performed at different temperatures for SUVs created with DPPC and treated with selected concentrations of fruit extracts of lowbush, highbush and wild bilberry [22,36,38,39]. Research conducted with the use of DPH probe has shown that tested substances neither change the main phase transition temperature nor fluorescence anisotropy, and thus the fluidity of membranes in the liquid-crystalline phase, as well as in the gel phase, compared with modified liposomes [38,39]. Extract of wild bilberry decreased slightly membrane fluidity in the gel phase, but increased it in the liquidcrystalline state.…”
Section: Discussionmentioning
confidence: 99%
“…Pretransition temperature (T p ) changes provide evidence for changes rather in the polar part of the membrane that result in loosening its structure [37,41,42]. Calorimetric studies were carried out with the membrane model in the form of MLVs formed of DPPC modified with the extracts and polyphenolic compounds [22,[36][37][38][39]. Calorimetric test results showed little change in T m only for very large concentrations of polyphenolic substances (10 mg mL -1 ), whereas for lower concentrations virtually no change was found.…”
Section: Discussionmentioning
confidence: 99%